‘Some of All of Us in You’: Intra-racial Relations, Pan-Africanism and Diaspora in Paule Marshall’s The Fisher King - López Ropero, Lourdes (Miscelánea: A Journal of English and American Studies, 2002)
Although it is the rise and fall of jazz in the African-American and black expatriate French scenes that shapes The Fisher King (2000), what really draws the reader’s attention in Caribbean-American Paule Marshall’s latest novel is her revisiting of her old Brooklyn neighbourhood of Bedford-Stuyvesant, the setting of her first novel, Brown Girl, Brownstones (1959). After recreating an ambience her readers are familiar with, Marshall engages in a much closer study of the long-standing rifts still breaching Brooklyn’s multi-ethnic black community —made up of ‘native’ blacks, Afro-Caribbean and Black Southern immigrants and their descendants— in the mid-1980s. Furthermore, for the first time in her writing career, Marshall touches upon black communities living in European, particularly French ghettoes. Thus, I argue that in focusing on diversity and conflict within black communities in US ghettoes and dwelling on their European counterparts, The Fisher King completes Marshall’s trajectory of widening and problematising the notion of the black subject and its community. I relate Marshall’s positioning to the recent debates over Pan-Africanism and diaspora led by cultural critics such as Paul Gilroy or Stuart Hall. Bringing into my discussion other novels by the author, I claim The Fisher King as an excellent companion to Brown Girl, Brownstones, through which Paule Marshall’s writing career comes full circle.
Keywords: Pan-Africanism; Diaspora; Ethnicity; Migration; Caribbean